2010
DOI: 10.1638/2009-0061.1
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Echocardiographic Evaluation of the Bottlenose Dolphin (Tursiops truncatus)

Abstract: In humans, fetal echocardiography represents the most important tool for the assessment of the cardiovascular well-being of the fetus. However, because of logistic, anatomic, and behavioral challenges, detailed fetal echocardiographic evaluation of marine mammals has not been previously described. Because the application of fetal echocardiography to cetaceans could have both clinical and academic importance, an approach to evaluating the fetal dolphin's cardiovascular status was developed with conventional, fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Fetal echocardiography was recently described in BN by Sklansky et al 19 The authors reported that a detailed assessment of fetal BN cardiovascular status, including 2D imaging and color flow mapping of the heart and great arteries as well as pulsed Doppler evaluation of the umbilical artery and vein, could be obtained between 8 and 9 months of gestation. 19 Another study, performed by the same authors on 4 adult BN trained to hold their breath following forced exhalation, showed that the TEE technique yielded high-quality images of the entire heart (atrioventricular and arterial valves, interatrial and interventricular septa, left and right atrial cavities, left and right ventricles, ascending aorta and main pulmonary artery). 4 The latter report also demonstrated mild tricuspid regurgitation in all BN, and mild aortic regurgitation in one BN using color flow Doppler mode.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal echocardiography was recently described in BN by Sklansky et al 19 The authors reported that a detailed assessment of fetal BN cardiovascular status, including 2D imaging and color flow mapping of the heart and great arteries as well as pulsed Doppler evaluation of the umbilical artery and vein, could be obtained between 8 and 9 months of gestation. 19 Another study, performed by the same authors on 4 adult BN trained to hold their breath following forced exhalation, showed that the TEE technique yielded high-quality images of the entire heart (atrioventricular and arterial valves, interatrial and interventricular septa, left and right atrial cavities, left and right ventricles, ascending aorta and main pulmonary artery). 4 The latter report also demonstrated mild tricuspid regurgitation in all BN, and mild aortic regurgitation in one BN using color flow Doppler mode.…”
Section: Discussionmentioning
confidence: 99%
“…Lacave showed how the diameters of the skull increase more slowly than the thoracic diameters, and that the thoracic diameters represent the limit of accuracy in late pregnancy [25]. Sklansky et al (2010) recognize the utility of fetal echocardiography as a safe technique able to evaluate the cardiovascular system in the bottlenose dolphin, especially in the period between the eighth and the ninth month of gestation. As in humans, this technique allows us to identify congenital cardiac anomalies [26][27][28] and to identify the possible causes of perinatal mortality risk associated with physiological abnormalities and cardiac hemodynamics [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Sklansky et al (2010) recognize the utility of fetal echocardiography as a safe technique able to evaluate the cardiovascular system in the bottlenose dolphin, especially in the period between the eighth and the ninth month of gestation. As in humans, this technique allows us to identify congenital cardiac anomalies [26][27][28] and to identify the possible causes of perinatal mortality risk associated with physiological abnormalities and cardiac hemodynamics [29,30]. In most cases, the optimal visualization of the fetal heart is obtained by positioning the pregnant female in lateral decubitus, homolaterally to the uterine horn in which the fetus is housed [26,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using conventional, portable ultrasound systems without sedation (Sklansky et al, 2010) have implemented fetal echocardiography between 8-9 months gestation. They concluded that fetal echocardiography can provide a safe and detailed assessment of the cardiovascular status of the fetal bottlenose dolphin.…”
Section: Respiratory System Affectionsmentioning
confidence: 99%